2002
DOI: 10.1097/00003246-200210000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Anti-interleukin-8 autoantibodies in patients at risk for acute respiratory distress syndrome

Abstract: Bronchoalveolar lavage fluid concentration of anti-interleukin-8:interleukin-8 complexes may serve as a marker of disease progression in patients at risk for acute respiratory distress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(144 citation statements)
references
References 8 publications
10
131
3
Order By: Relevance
“…80,81 In one study, outcome from ARDS was better predicted by levels of IL-8:anti-IL-8 autoantibody complexes than levels of IL-8 alone, 81 even though complexing of anti-IL-8 antibody with IL-8 neutralizes its neutrophil chemotactic activity. 82 Recently the upstream regulation of transcription of proinflammatory cytokines and mediators has become a focus of pathogenetic research in ALI/ARDS. Nuclear factor kappa-B (NFkB), a transcription factor that regulates the expression of ICAM-1, IL-1b, IL-6, IL-8, and TNF-a, among others, 83,84 has been the most widely studied.…”
Section: Cytokine-mediated Inflammation and Injurymentioning
confidence: 99%
“…80,81 In one study, outcome from ARDS was better predicted by levels of IL-8:anti-IL-8 autoantibody complexes than levels of IL-8 alone, 81 even though complexing of anti-IL-8 antibody with IL-8 neutralizes its neutrophil chemotactic activity. 82 Recently the upstream regulation of transcription of proinflammatory cytokines and mediators has become a focus of pathogenetic research in ALI/ARDS. Nuclear factor kappa-B (NFkB), a transcription factor that regulates the expression of ICAM-1, IL-1b, IL-6, IL-8, and TNF-a, among others, 83,84 has been the most widely studied.…”
Section: Cytokine-mediated Inflammation and Injurymentioning
confidence: 99%
“…In several studies, neutropenia has been shown to attenuate the extent of lung damage (2, 3), highlighting the pivotal role of PMN recruitment in the early development of the disease. The human CXCR2 (and CXCR1) ligand CXCL8 is produced in the BAL of patients with ARDS and largely accounts for its chemotactic activity (9). Moreover, CXCL8 levels in the BAL have been demonstrated to affect prognosis of ARDS.…”
Section: Cells (mentioning
confidence: 99%
“…Both chemokines are functional homologs of human CXCL8 (IL-8), which has been associated with the development and outcome of ARDS (9,10). Upon activation, CXCR2 is phosphorylated, leading to receptor desensitization and internalization, intracellular removal of the ligand, and finally, degradation or re-expression of the receptor on the cell membrane (11).…”
Section: Introductionmentioning
confidence: 99%
“…3 The main known property of IL-8 is to induce neutrophil activation, and anti-IL-8 autoantibodies have been shown to inhibit IL-8 interaction with its specific receptors on neutrophils. 6 IL-8 also binds to heparin, 7 and there may be IL-8 receptors on platelets. [8][9][10] This study was undertaken to investigate whether antibodies to IL-8 are able to induce platelet activation in vitro and whether they are dependent on heparin.…”
Section: Introductionmentioning
confidence: 99%